Восприятие информации студентами вуза в ходе социально-психологического тренинга коммуникации - Попова, Галина Викторовна; Ковалева, И. Б. (Impressum, 2020)
In the article it is discussed the peculiarities of the university students' perception of information of various types in the process of training communication. The information of the personal and program type is identified. The research data on the perception of different types of information by the training participants with different sociometric status in the study group is presented.
Keywords: социально-психологческий тренинг; деловая коммуникация; социометрический статус студента; личностно ориентированная информация; программная информация; socio-psychological training; business communication; sociometric status of the university student; personally oriented information; programmatic information